Fully Textile X‐Ray Detectors Based on Fabric‐Embedded Perovskite Crystals. Issue 15 (14th April 2022) - Possanzini, Luca; Basiricò, Laura; Ciavatti, Andrea; Tessarolo, Marta; Fraboni, Beatrice
Abstract: The interest and thrust for wearable ionizing radiation dosimeters are rapidly growing, stimulated by a large number of different applications impacting on humankind, spanning from medicine to civil security and space missions. Lead halide perovskites are considered one of the most promising classes of novel materials for X‐ray detectors due to their superior electronic and detection performance coupled with compatibility with solution‐based printing processes, allowing fabrication onto flexible substrates. It is reported on fully textile perovskite‐based direct X‐ray detectors, where the photoactive layer is constituted by a silk‐satin fabric functionalized with methylammonium lead bromide perovskite crystals embedded in the textile. The reliability of the proposed fabrication process, based on simple and low‐tech deposition techniques adaptable to industrial printing technologies for textiles, is assessed by realizing different detector's architectures that exhibit comparable detection performances. Sensitivity values up to (12.2 ± 0.6) µC Gy −1 cm −2 and a limit of detection down to 3 μGy s −1 are achieved, and low bias operation (down to 1 V) is demonstrated, validating wearable applications. Further, fully textile pixelated matrix X‐ray sensors are implemented and tested, providing the proof of principle for large‐area scalability. Abstract : A fully textile perovskite‐based direct X‐ray detector is presented. The low‐bias operation, lightweight, and the employment of natural fabrics, such as silk‐satin and cotton, assure the comfort and breathability for the effective application of this new class of textile sensors as wearable ionizing radiation dosimeters, which can be directly realized into smart garments.